2020
DOI: 10.1101/2020.08.04.20168328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha-synuclein seeds in olfactory mucosa of patients with isolated rapid-eye-movement sleep behaviour disorder

Abstract: Isolated REM sleep behaviour disorder is an early-stage alpha-synucleinopathy in most, if not all, affected subjects. Detection of pathological alpha-synuclein in peripheral tissues of isolated REM sleep behaviour disorder patients may identify those progressing to Parkinson's disease, dementia with Lewy bodies or multiple system atrophy, with the ultimate goal of testing preventive therapies. Real-Time Quaking-Induced Conversion provided evidence of alpha-synuclein seeding activity in cerebrospinal fluid and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Compared to the previously reported RT-QuIC results in OM of patients with PD and MSA, and iRBD, the RT-QuIC sensitivity in DLB is apparently higher. 20 , 21 This finding might be related to the detection of α-syn deposition in the olfactory neuroepithelium of DLB individuals. 34 …”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Compared to the previously reported RT-QuIC results in OM of patients with PD and MSA, and iRBD, the RT-QuIC sensitivity in DLB is apparently higher. 20 , 21 This finding might be related to the detection of α-syn deposition in the olfactory neuroepithelium of DLB individuals. 34 …”
Section: Discussionmentioning
confidence: 88%
“…We performed α-syn RT-QuIC assay as reported previously for CSF and OM except where indicated. 12 , 21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another key factor related to sleep disorders is α-syn ( Dolores et al, 2016 ). Abnormal α-syn, normally localized to presynaptic terminals of neurons, forms pathological amyloid aggregates deposited in multiple brain regions and induces abnormal neurotransmitter release, such as sleep-related interleukins ( Dolores et al, 2016 ; Doppler et al, 2017 ; Garrido et al, 2020 ; Stefani et al, 2021 ). Phosphorylated α-syn deposits in the colon, saliva, glands, and skin can be used to differentiate subjects with isolated rapid eye movement sleep behavior disorder (RBD) from controls with 24–89% sensitivity and 78–100% specificity ( Doppler et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of sleep depends on the comprehensive functions of multiple brain regions and a series of neurotransmitters, including dopamine, 5-hydroxytryptamine, norepinephrine, and other PD-related molecules ( Alexandre et al, 2006 ; Meles et al, 2017 ; Oh et al, 2018 ; Hayat et al, 2020 ). The mechanism of sleep disorders in PD patients may involve the loss of DA neurons and the deposition of α-syn in the brain stem, basal ganglia and hypothalamus ( Dolores et al, 2016 ; Doppler et al, 2017 ; Garrido et al, 2020 ; Stefani et al, 2021 ). It has been suggested that sleep disorders have a certain value for the prediction and diagnosis of PD ( Barasa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%